TINJAUAN YURIDIS PENEGAKAN HUKUM TERHADAP PELAKU PEMERKOSAAN ANAK DIBAWAH UMUR DI HUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK - Yeni Nuraeni; Deni Heriawan (Universitas Majalengka, 2023)
It is undeniable that the increasingly sophisticated advances in technology can no longer be overcome. We all agree that technological advances, especially in Indonesia, have touched all levels of society. This has brought a change in new lifestyles, but most of our society is not fully prepared to face the advances in technology, many of which are misused. One tangible form of technological progress is the ease of accessing the internet which encourages people, especially teenagers, to access pornographic actions and pornography. This has caused moral damage to the generations of the Indonesian people and this has also become one of the reasons for the rise of criminal cases, for example the rape of both adults and children. Based on this, the identification of the problems that will be examined in this study is about law enforcement for the rape of minors and legal remedies in dealing with the rape of minors. The purpose of this study was to find out about the law enforcement of rape of minors and legal efforts to deal with the rape of minors. The approach used is a juridical approach. The data used in this study are secondary data obtained from literature studies. After the data is collected, and analyzed qualitatively. From the results of this study it can be concluded that the criminal acts of rape that occurred lately often occur and those who are victims not only to adults but the perpetrators of crimes often target minors to be imprisoned. Criminals use telecommunication tools based on modern technology, because through social networks to ensnare victims they are easily deceived by lure and so on.